Encontros e desencontros entre personagens em um museu de ciências: entre o realizado e o possível - Reis, Flávia Machado dos (2015)
Museums and Sciences Centers are considered non-formal spaces of education because in these places may occur educational actions that are difference from the activities that are generally developed in school. Teachers, who are willing to take their students to these spaces, contribute not only to the acquisition of knowledge related to the science, but also to the cultural formation and development of their students. However, few studies have analyzed the role of a teacher in the preparation and monitoring of the visit to the museum, as well as the relations between the museum and the school. In this sense, the proposed workhad as a general objective to comprehend the relationsthat there are between science teachers and the educational group of The Cerrado Biodiversity Museum (MBC) as regard to the monitored visits of the students of Basic Education. The studies of cases were done with two sciences teachers from the public state system education in Uberlândia who visited the MBC with their students. The observations were made in the MBC and in the schools before and after the visits, and after the visits semi structured interviews and questionnaires have been applied in order to collect data. We also conducted interviews with the mediators and the coordinators of the educationalexhibition site. The data were analyzed according to the methodological and theoretical proposal of content analysis. The expectations of the educational museum staff in relation to school visits are that: both students and teachers interact with the resources available in the museum and the visit should be a moment of acquisition and expansion of information and culture, but the teachers must be pedagogical responsible for the organization and leading the visit. The coordinators also hope that the teachers who visit the site with their students take ownership of the museum. The sciences teachers indicatethat they obtain information about the MBC through the previous visits and through invitations; and regarding to the organization and planning of the visit, the teachers concern with the logistic aspects that are the preparation of the students in classroom giving them information about dates and schedules of visits and, mainly, how they do behavior in the museum. The motives and interests of the teachers to visit the museum are connectedto the contents of science that can be visualized in the museum and the possibility of the student to learn more about it. However, at the moment of the visit teachers leave to the mediators all the concerning about how to deal with the activities during the visit in the museum. Returning to school, one teacher only verify the answers from the evaluative questionnaire proposed for the activity, and the other teacher did not make any different activity in order to deployment the visit. To the teachers, the educational function/role of the MBC is to enable students to interact with the objects and views/concepts also presented by the mediators. The teachers still conceive the museum as a space of learning, where is possible to work scientific concepts, boost sciences class, attract the attention of the student, "prove" the sciences content and live experience. The mediators still assign to the educational potential of the museum the possibility to ally theory and practice, to live and see the experience, to promote closer ties with students, to contribute to the scientific knowledge of the population, and to be a source to enlarge the scientific culture. Both teachers and the mediators realize that there is still lacking of interaction between the museum and schools. Lastly, we emphasize that the participating teachers of this research do not appropriate from the visit planning to the MBC, and the ownership of the museum space and its activities occurred as leisure and internment time and ithas not seen as a space of can be enlarge the pedagogical practice of the teachers to their own training.